Model Toleransi Antar Umat Beragama Di Desa Gading Rwvii Kecamatan Tambak Sari Kota Surabaya - Rahmad Yulianto; A. Tohari (Al Hikmah, 2019)
AbtractIndonesia is a country rich in deversity. Differences in ethnicity, culture, custum, lnguange, and religion make Indonesia defferent from other countries. To realize and support multiculturism in Indonesia, tolerance and mutual respect are needed. This model of tolerance among religious people could be realized in Indonesia as an example in Gading, Tambaksari, Surabaya.Gading is a plural illage in terms of culture and religion. It consists of 12 RTs, te people have believed on two religions, such as Islam as the religion of the majority and one religion, Christianity. The people’s life of Gading seems very harmonious and peaceful. For centuries they have been living there without conflictson religion. For local peoole, the existence of mosquse and churches thet are almost side by side does not cause inter-religious problems. In a village of 2,500 people, this indicated that villagers were not followers of one religion. “Respect for each other has been by citizens”, the “Pancasila Village” was named after the village as a conclusion from this study  about tolerance between religious peopole in Gading and can still be well maintained.  Keywords: Interfaith Model, tolerance, tolerance, different religious people